2022
DOI: 10.3390/lubricants10120348
|View full text |Cite
|
Sign up to set email alerts
|

Three-Body Abrasive Wear Performance of High Chromium White Cast Iron with Different Ti and C Content

Abstract: The need for better wear-resistant materials to reduce cost and save the environment is noteworthy. The striking wear resistance of high chromium white cast iron (HCCI) has made it industry’s predominant choice. The three-body abrasive wear resistance performance of HCCI was investigated based on combined Ti and C. The Ti and C content varied in different percentages. The addition of Ti resulted in refined M7C3 carbides and TiC crystallization. The hardness was significantly affected by the addition of Ti. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…In addition, some small-size debris and embedded particles can flake off during cyclic rubbing, which can lead to three-body abrasive wear to the silver conductor, as presented in figure 9(G), which demonstrates intensive signs of particle ploughing and rolling as well as pits. Similar morphology caused by three-body abrasive wear in metal has been reported by Huq et al [30]. The variation in surface height and roughness is also a factor for accelerating the moving of flaked particles between the steel sheet and conductor.…”
Section: Failure Mechanismsupporting
confidence: 81%
“…In addition, some small-size debris and embedded particles can flake off during cyclic rubbing, which can lead to three-body abrasive wear to the silver conductor, as presented in figure 9(G), which demonstrates intensive signs of particle ploughing and rolling as well as pits. Similar morphology caused by three-body abrasive wear in metal has been reported by Huq et al [30]. The variation in surface height and roughness is also a factor for accelerating the moving of flaked particles between the steel sheet and conductor.…”
Section: Failure Mechanismsupporting
confidence: 81%
“…The relatively high cost-effectiveness of HCCI compared to some other wear-resistant materials results in it being an excellent wear-resistant material, and it is widely used in many applications [6,[9][10][11][12][13][14][15][16][17][18][19]. This is because HCCI typically exhibits a hardness of between 650 and 850 HV.…”
Section: Introductionmentioning
confidence: 99%
“…However, the addition of a small amount (up to 3.47%) of Nb contributes to the hardness and wear resistance of the HCCI [14,15], and vanadium (V) [13] also has this effect. Furthermore, the addition of 2 wt.% titanium (Ti) can also refine the M 7 C 3 carbide [17,19]. However, R. J. Chung et al also reported that the M 7 C 3 carbide was not refined at 6% Ti content.…”
Section: Introductionmentioning
confidence: 99%
“…High-stress abrasion occurs when abrasive particles are fractured between two solid surfaces [6,36]. In wet grinding practice, high-stress abrasion occurs over a small region when ore particles are trapped between the grinding balls and the mill liner, and the load is sufficient to fracture abrasive particles (three-body abrasive wear) [37]. The high contact pressure produces indentations and scratching of the surface and pulverizes the abrasive ore particles such that wear of liners and grinding balls occurs by combined abrasion and corrosion [10,27,38,39].…”
Section: High Stress Wear (Abrasion-corrosion)mentioning
confidence: 99%